2015
DOI: 10.1039/c5nr00327j
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sorting of differently charged chitosan derivatives and chitosan-based nanoparticles

Abstract: Chitosan (Chi) is a biodegradable nontoxic polycation with multiple reactive groups that is easily used to obtain derivatives with a desired charge and hydrophobic properties. The aim of this work was to study the intracellular traffic of positively charged hexanoyl-chitosan (HC) or HC-based nanoparticles (HCNPs) and negatively charged succinoyl-chitosan (SC) and SCNPs in epithelial and macrophage cell lines. By using flow cytometry we demonstrated that positively charged HC adhered to cell membranes quicker a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 54 publications
(110 reference statements)
3
15
0
Order By: Relevance
“…Chitosan-coated particles were taken up better than particles without chitosan, proving that the cationic surface may improve the intracellular uptake. The former particles also showed stronger accumulation in lysosomes as observed by LysoTracker reda cationic fluorescent dye that accumulates in acidic compartments as an indicator of lysosomal content, a behavior also described by others (43). While the lysosomal degradation of PLGA nanocarriers remains to be investigated in more detail, the co-localization with lysosomes is at least likely to enhance drug release and polymer degradation (30), also contributing to the safe elimination of such nanocarriers.…”
Section: Discussionsupporting
confidence: 66%
“…Chitosan-coated particles were taken up better than particles without chitosan, proving that the cationic surface may improve the intracellular uptake. The former particles also showed stronger accumulation in lysosomes as observed by LysoTracker reda cationic fluorescent dye that accumulates in acidic compartments as an indicator of lysosomal content, a behavior also described by others (43). While the lysosomal degradation of PLGA nanocarriers remains to be investigated in more detail, the co-localization with lysosomes is at least likely to enhance drug release and polymer degradation (30), also contributing to the safe elimination of such nanocarriers.…”
Section: Discussionsupporting
confidence: 66%
“…32 Earlier, we have shown that positively charged C and Cbased NPs poorly penetrated epithelial cells and were engulfed mostly by macrophages. 33 At the same time, negatively charged succinylchitosan and corresponding NPs easily penetrated all types of cells and were transported into lysosomal compartment. Based on our earlier results and the results obtained in this study, it can be hypothesized that CP via cytosolic pathway is effective for positively charged molecules.…”
Section: In Vivo Effect Of L-based Npsmentioning
confidence: 98%
“…Further, Zubareva et al. [ 100 ] investigated the influence of the surface charge of ChNPs on their fate and cellular uptake by MIAPaCa‐2 cells and RAW264.7 cells. To this end, positively charged ChNPs, composed of hexanoyl chitosan (HCh), and negatively charged ChNPs made of succinoyl chitosan (SCh), were generated.…”
Section: Cellular Uptake Studies and Drug Delivery Systemsmentioning
confidence: 99%